Developing project-based e-module for contextual written language skills course at English language education study program - Rika; Saragih, Anggraini T; Haswani, Fahri; Erlita, Yeni (UNIB Press, 2024)
The ability to develop, project-based e-modules for the Contextual Written Language Skills course in a learning context into another learning context is anessential ability for students based on project-based learning. However, the learning pattern used is innovative learning, which can improve students’ skills and thinking abilities. The ability of project-based e-modules for the English lecturers to adapt their knowledge and skills from project-based e-modules for the Contextual Written Language Skills course to another course has been studied. This research focused on the presentation of discussion material that is not accompanied by an assignment or project or the systematics of preparing teaching materials and e-modules using project-based learning for Contextual Written Language Skills. The research used in this study is the Research and Development (RnD) development model by adopting the model Borg and Gall, which consists of 6 phases: 1) Gathering data and Information, 2) Need analysis, and 3) Material Design. 4) Validating by experts, 5) Revising, and 6) Final Product. The results of this study are based on an analysis of the needs of students who experience limited digital learning resources related to the material in the Contextual Written Language Skills course. Therefore, researchers are interested in developing textbooks in the form of e-modules to meet the needs of students and improve their learning outcomes. E-modules developed were validated by experts. Material expert validation had an average score of 88,61%, which was classified as very good. Media expert validation obtained an average score of 87,75% which was classified as very good. This means that the developed e-module is valid to be used in the Contextual Written Language Skills course.